Changes in Local Atrial Electrograms and Surface ECG Induced by Acute Atrial Myocardial Infarction - Amorós-Figueras, Gerard (Front Physiol, 2020)
BACKGROUND: Atrial coronary branch occlusion is a hardly recognizable clinical entity that can promote atrial fibrillation. The low diagnostic accuracy of the ECG could deal with the characteristics of the ischemia-induced changes in local atrial electrograms, but these have not been described. OBJECTIVES: We analyzed the effects of selective acute atrial branch occlusion on local myocardial structure, atrial electrograms, and surface ECG in an experimental model close to human cardiac anatomy and electrophysiology. METHODS: Six anesthetized open-chest anesthetized pigs underwent surgical occlusion of an atrial coronary branch arising from the right coronary artery during 4 h. Atrial electrograms and ECG were simultaneously recorded. One additional pig acted as sham control. In all cases, the hearts were processed for anatomopathological analysis. RESULTS: Atrial branch occlusion induced patchy atrial necrosis with sharp border zone. During the first 30 min of occlusion, atrial electrograms showed progressive R wave enlargement (1.8 ± 0.6 mV vs. 2.5 ± 1.1 mV, p < 0.01), delayed local activation times (28.5 ± 8.9 ms vs. 36.1 ± 16.4 ms, p < 0.01), ST segment elevation (−0.3 ± 0.3 mV vs. 1.0 ± 1.0 mV, p < 0.01), and presence of monophasic potentials. Atrial ST segment elevation decreased after 2 h of occlusion. The electrical border zone was ∼1 mm and expanded over time. After 2 h of occlusion, the ECG showed a decrease in P wave amplitude (from 0.09 ± 0.04 mV to 0.05 ± 0.04 mV after 165 min occlusion, p < 0.05) and duration (64.4 ± 8.0 ms vs. 80.9 ± 12.6 ms, p < 0.01). CONCLUSION: Selective atrial branch occlusion induces patchy atrial infarction and characteristic changes in atrial activation, R/S wave, and ST segment that are not discernible at the ECG. Only indirect changes in P wave amplitude and duration were appreciated in advanced stages of acute coronary occlusion.